Customer Satisfaction Index (CSI) of Gojek User Post Fuel Prices Changes - Aloysius Rangga Aditya Nalendra; Slamet Heri Winarno; Agus Priadi; Imelda Sari (Jurnal Manajemen dan Kewirausahaan, 2022)
This study  aims to  examine the correlation between fuel prices and service tariffs towards customer satisfaction. This study is conducted at post fuel price changes. The sample of this study uses Simple Random Sampling as 86 respondents. The result shows that the biggest factor which gives much impact to customer satisfaction is service tariff variable.  The study findings highlight the significant and positive of fuel prices and service tariffs towards consumer service or so-called customer satisfaction.